Investigation of cylinder pre-treatments for the stability of ammonia gas reference materials - di Meane, Elena Amico; Brown, Richard J. C.; Brewer, Paul J.; Ferracci, Valerio; van Wijk, Janneke I. T. (Springer, 2022)
This report describes work to evaluate the performance of different commercial and proprietary cylinder treatments in improving the stability of ammonia reference materials in high pressure cylinders. Gas mixtures of 100 µmol/mol and 10 µmol/mol ammonia in nitrogen were prepared gravimetrically at both NPL and VSL. Comparative measurements at each amount-of-substance fraction were used to assess which passivation technique minimised the loss of ammonia upon preparation. The results indicate little difference between the commercial treatments, except at lower amount-of-substance fractions (10 μmol/mol). The variation observed in performance might be explained by the different abilities of the various treatments to prevent the adsorption of ammonia molecules on the internal surfaces of the cylinder, although the role of residual water on the cylinder surface in reacting with ammonia is unclear.
Keywords: gas reference materials; stability; cylinder passivation; ammonia